2017
DOI: 10.1007/s11244-017-0851-8
|View full text |Cite
|
Sign up to set email alerts
|

Probing Oxide Reduction and Phase Transformations at the Au-TiO2 Interface by Vibrational Spectroscopy

Abstract: transformations might be both thermally or light induced, however, the colloidal deposition synthesis of the Au/TiO 2 catalysts is clearly ruled out as cause for the formation of the reduced phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 70 publications
7
12
0
Order By: Relevance
“…Bandgaps became smaller for TiO2-AuNP composites upon ps-532-nm irradiation, and the decrease was more pronounced with more gold. We obtained slightly lower bandgaps for TiO2 with nominally 3 wt% AuNPs compared to neat TiO2, even without laser processing, indicative of rutilization by AuNP physisorption, in line with observations by Strunk et al 92 and Jovic et al 52 We explain the observed decrease of TiO2 bandgaps as a function of AuNP loading and ps-532-nm laser energy dose by electric field enhancements that are most pronounced near the interface between AuNP and TiO2, similar to our ZnO results (conceptual details are illustrated in Figure 6).…”
Section: Tio2 Materialssupporting
confidence: 92%
“…Bandgaps became smaller for TiO2-AuNP composites upon ps-532-nm irradiation, and the decrease was more pronounced with more gold. We obtained slightly lower bandgaps for TiO2 with nominally 3 wt% AuNPs compared to neat TiO2, even without laser processing, indicative of rutilization by AuNP physisorption, in line with observations by Strunk et al 92 and Jovic et al 52 We explain the observed decrease of TiO2 bandgaps as a function of AuNP loading and ps-532-nm laser energy dose by electric field enhancements that are most pronounced near the interface between AuNP and TiO2, similar to our ZnO results (conceptual details are illustrated in Figure 6).…”
Section: Tio2 Materialssupporting
confidence: 92%
“…Furthermore, the interface structure may be rather different in the core-shell system compared to samples prepared by the colloidal deposition route, in which reduction and rutile formation of the interface has recently been observed. [31] No mechanistic studies were conducted here, but the roughly equal amounts of CO and CH 4 formed photocatalytically may be indicative for the decomposition of ac ommon intermediate in the mechanism. One option may be acetaldehyde, suggested previouslya si ntermediate on bare TiO 2 .…”
Section: Discussionmentioning
confidence: 93%
“…Electromagnetic fields caused by light irradiation of the core–shell metal‐semiconductor‐metal structure may be very different from those caused in conventional Au/TiO 2 catalysts. Furthermore, the interface structure may be rather different in the core–shell system compared to samples prepared by the colloidal deposition route, in which reduction and rutile formation of the interface has recently been observed …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations